Challenges and Solutions for Education in Aceh: Perspective of Dayah Education - Ilyas, Mukhlisuddin; Munawar, M; Islami, Nurul (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2024)
The educational framework in Aceh exists within a broader national system, yet lacks a unified conceptual foundation to guide its various stakeholders. Instead, disparate visions operate in isolation, often left unrealized. A deeper philosophical approach is needed—one that fosters a dynamic and integrated model of education capable of cultivating competent and professional individuals. The overlap and indistinct boundaries between institutions further blur the path to innovation, reinforcing structural inefficiencies. A truly holistic system must transcend the conventional divisions between secular and religious education, creating a seamless integration of knowledge that embodies a higher universal principle. This calls for an overarching governance structure—an entity that dissolves institutional dichotomies and redefines management under a singular, cohesive vision. The persistence of dual systems has perpetuated fragmentation, hindering the holistic development of Aceh’s youth. To move forward, a synthesis of curriculum, policy, and resource allocation must be embraced, uniting all aspects of education under a singular, purpose-driven paradigm.